Implementation and Impact of Human Resources Development in Improving the Performance of Teachers in Schools (Multi Case Studies) - Muh Burhanudin Harahap; Maria Veronika Roesminingsih; Mudjito (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
This research aims to analyze the implementation and impact of human resource development in improving the performance of students. This research used a qualitative approach with the type of multi-case study research at the Elementary School Muhammadiyah of 1 Jember and the Elementary School Al Baitul Amien of 1 Jember. Data collection was carried out by observation, interviews, and documentation in both schools. The data analysis process was carried out by condensing data, presenting data, drawing conclusions, and verification. Based on the research conducted, it was concluded that the implementation of human resources in Elementary School Muhammadiyah of 1 Jember and Elementary School Al Baitul Amien of 1 Jember, namely 1) The school has fully professional development of educators in the form of training programs and always strives to improve the quality of education through skills improvement programs. 2) The school activity program is always maximized, through habituation in improving the quality of learning through activities, teaching, during the learning process and up to the implementation of quality training so that it is optimal. 3) Programmed school activities program in a clear concept in planning the skills development of educators. 4) Regulations concerning the development of written and straightforward teaching staff and maximized for the program of enhancing the skills of educators which are compiled through the formulation and determination of collective teacher teamwork. Then the impact of the development of human resources in improving the performance of students has a good overall impact on every program implementation of the two schools.